Peningkatan Minat dan Hasil Belajar Siswa Melalui Penerapan Model Pembelajaran Problem Based Learning Menggunakan Quizizz - Aprianti, Wiyana; Rohandi, Manda; Azhar Kadim, Ahmad (JURNAL PTI (PENDIDIKAN DAN TEKNOLOGI INFORMASI) FAKULTAS KEGURUAN ILMU PENDIDIKAN UNIVERSITA PUTRA INDONESIA "YPTK" PADANG, 2024)
This research aims to increase students' interest and learning outcomes through the application of the Problem Based Learning (PBL) Learning Model assisted by the Quizizz application. This research is a Class Action Research (PTK) conducted in class X2 of SMA Negeri 1 Kabila in the subject of Informatics, especially in the Selection Sort sub-material which is carried out in two cycles. The data collection techniques in this study include learning outcome tests, observations, and questionnaires to measure students' interest in learning. Data analysis was carried out using descriptive statistical analysis. In the first cycle, students' initial interest in learning was in the high category of 46.6%, medium 53.3%, and low 0%. The learning outcomes in the first cycle showed an average score of 72.23 with classical completeness of 46.66%. In the second cycle, there was a significant increase where students' interest in learning reached 100% in the high category and the learning outcomes showed an average score of 83.43 with 100% classical completeness. The Wilcoxon test showed a significance value of 0.000 which means it was less than 0.05 so the research hypothesis was accepted. These results show that the application of the PBL learning model with the support of the Quizizz application significantly increases students' interest and learning outcomes. This study emphasizes the importance of using interactive and innovative learning methods in increasing the effectiveness of learning in the classroom.